Phenomenographic Study of Studentsâ€™ Manipulative Skills During Transition from Primary to Secondary School (Sains Humanika, 2013)
Manipulative skills include skills in handling materials and apparatus in the context of scientific investigation. Students lack exposure in â€œhands-onâ€ activities at primary school lead to insufficient manipulative skills and they may carry this problem with them to secondary school. This problem will pose a greater problem during school transition. School transition is a challenging process for students whereby they have to adapt with social issues to fit into their new environment. This study resulted from a longitudinal study with the implementation of phenomenographic research design. The research was administered to 10 primary school students (Year Six) and they were re-interviewed in secondary school (Form One). Studentsâ€™ capability in handling thermometer, measuring cylinder, Bunsen burner and microscope were observed in order to get comprehensive understanding of studentsâ€™ manipulative skills during the process of transition from primary to secondary school. Findings revealed that students have not fully developed the basic skills in using and handling scientific apparatus. Five (5) categories of description emerged from data that represented the nature of the studentsâ€™ manipulative skills, namely: (1) non-systematic operation of tasks, (2) non-effective management of time and workplace, (3) haphazard safety and precautionary measures, (4) poor technical skills, and (5) problem in numeracy and drawing specimen.
Keywords: Transition from primary to secondary school; progression in science learning; manipulative skills; science psychomotor skills; phenomenography